Expansion of the 'seeds without borders' agreement to Bhutan - CGIAR Research Program on Rice (2018)
Bhutan can now import improved variety seeds without much hassle from six countries in the region. Bangladesh, Cambodia, India, Myanmar, Nepal, and Sri Lanka are the other members of the network agreement.